2021
DOI: 10.1038/s41467-021-21228-x
|View full text |Cite
|
Sign up to set email alerts
|

Simple physical mixing of zeolite prevents sulfur deactivation of vanadia catalysts for NOx removal

Abstract: NOx abatement has been an indispensable part of environmental catalysis for decades. Selective catalytic reduction with ammonia using V2O5/TiO2 is an important technology for removing NOx emitted from industrial facilities. However, it has been a huge challenge for the catalyst to operate at low temperatures, because ammonium bisulfate (ABS) forms and causes deactivation by blocking the pores of the catalyst. Here, we report that physically mixed H-Y zeolite effectively protects vanadium active sites by trappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…Selective catalytic reduction of nitrogen oxides (NO x ) using NH 3 as the reducing agent (NH 3 -SCR) is commercially utilized to control the NO x emissions from exhausts in the presence of O 2 . Vanadium oxide-based catalysts (V 2 O 5 -WO 3 /TiO 2 ) are typically employed as industrial catalysts in stationary deNO x systems for power plants and waste treatment plants, whereas Cu-exchanged zeolites, such as Cu-CHA, are utilized in urea-based SCR systems in diesel vehicles. Inomata et al recently reported that unsupported bulk vanadium oxides and tungsten-doped vanadium oxides exhibit higher NO-conversion capabilities than those of conventional TiO 2 -supported vanadium catalysts for NH 3 -SCR at low temperatures (<150 °C). Although these catalysts are considered the state of the art, catalytic activities, especially at low temperatures, must be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Selective catalytic reduction of nitrogen oxides (NO x ) using NH 3 as the reducing agent (NH 3 -SCR) is commercially utilized to control the NO x emissions from exhausts in the presence of O 2 . Vanadium oxide-based catalysts (V 2 O 5 -WO 3 /TiO 2 ) are typically employed as industrial catalysts in stationary deNO x systems for power plants and waste treatment plants, whereas Cu-exchanged zeolites, such as Cu-CHA, are utilized in urea-based SCR systems in diesel vehicles. Inomata et al recently reported that unsupported bulk vanadium oxides and tungsten-doped vanadium oxides exhibit higher NO-conversion capabilities than those of conventional TiO 2 -supported vanadium catalysts for NH 3 -SCR at low temperatures (<150 °C). Although these catalysts are considered the state of the art, catalytic activities, especially at low temperatures, must be improved.…”
Section: Introductionmentioning
confidence: 99%
“…4 In contrast, Mo 1 /TiO 2 can decompose ABS at temperatures as low as 225 °C, far lower than the reported lowest dew point of ABS. 15 Because both Mo and Ti of Mo 1 /TiO 2 are also important components of commercial V 2 O 5 –MoO 3 /TiO 2 SCR catalysts, Mo 1 /TiO 2 provides a crucial base for designing strong ABS-resistant SCR catalysts typically applied in many industrial boilers, as further confirmed by the high stability of the Mo 1 /TiO 2 catalyst under simulation stack gas conditions of industrial boilers (Fig. S11†).…”
Section: Resultsmentioning
confidence: 87%
“…ABS deposited on active sites is reported to be usually decomposed in a relatively high temperature range owing to its viscosity and the electrostatic attraction between NH 4 + and HSO 4 − . 13–15 Two kinds of interaction are often important factors to determine the temperatures required for ABS decomposition: ABS-catalyst adsorption interactions and NH 4 + –HSO 4 − electrostatic interactions. Conventional methods are often focused on the interactions between ABS and catalysts and thus the lowest decomposition temperature for ABS was reported to be ∼340 °C.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Unfortunately, both technologies are ineffective for NOx abatement at temperatures below 200°C due to the slow oxidation of NO to NO2, the unsatisfactory activity of NO reduction, incomplete decomposition of urea to gaseous NH3, and the potential deactivation due to ammonium-nitrate salts deposition. [6][7][8][9][10] One feasible strategy is passive NOx adsorption (PNA), which traps NOx at low temperatures and releases it thermally at high temperatures where NSR or SCR catalysts start working. Johnson Matthey Inc. first reported the potential of zeolite supported Pd catalysts as efficient NO storage materials.…”
Section: Introductionmentioning
confidence: 99%